Molecular identiﬁcation of lactic acid bacteria with probiotic properties isolated from the posterior intestine of Nile tilapia (Orechromis niloticus) - Castañeda, Arnaldo E. (2018)
Probiotic bacteria in aquaculture represent a control alternative and prevention of pathogens, in addition, reduce the use of antibiotics. However, it is necessary to search for other groups of bacteria with similar or better properties, obtained even from the same source. The aim of the study was to identify molecularly lactic acid bacteria with probiotic properties isolated from the posterior intestine of Nile tilapia (Oreochromis niloticus). The study was carried out from November 2017 to March 2018 evaluating the antagonistic, proteolytic, amylolytic, and antibiotic sensitivity activities, and antagonistic to the following pathogens: Aeromonas hydrophila, Aeromonas veronii, Pseudomonas aeruginosa, Pseudomonas putida and Plesiomonas shigelloides. It was identified by sequencing the 16S rRNA gene that Enterococcus faecium (IP5-2a) and Pediococcus pentosaceus (IP5-2b) inhibited the growth of pathogens, in addition, were sensitive to the antibiotics chloramphenicol, amoxicillin/clavulanic acid, gentamicin, erythromycin and tetracycline, respectively. The results show that E. faecium and P. pentosaceus possess the best antagonistic activities, property of greater relevance to determine a potentially probiotic bacterium. Therefore, it is concluded that the bacteria identified in the present study are good candidates to be considered probiotic, however, it is necessary to confirm their in vivo properties.